Museologia decolonial: um olhar para museu de artes visuais do Maranhão - REIS, Sunshine Cristina de Castro (2025)
Decoloniality is a field under construction and in dispute, both in theoretical and practical terms. It is an academic and political project of problematization and disobedience that emerges as a confrontation with the modulation of being, knowledge, and power. Therefore, its applicability in museology requires confronting the status of sanctuary assigned to the preservation of memory, which remains isolated from the disorder of the world. This is a rhetorical inversion that conceals the production and reproduction of historical social injustices through the projection of neutrality, which disguises the ideological, political, and economic battlefield in which it is immersed. In this sense, the present investigation is situated within Research Line 2: Culture, Education, and Technology, with the aim of identifying decolonial actions and contributions to diversity and equity developed by the Museum of Visual Arts of Maranhão. The research is based on an interdisciplinary investigation with two levels of analysis. The first focuses on the collection available for contemplation, with emphasis on the space dedicated to Indigenous peoples, Afro-Maranhense communities, and women. The second examines daily practices and the perspectives of contemporary artists such as Pablo Monteiro, Silvana Mendes, Ingrid Barros, Gê Viana, and Genilson Guajajara, in relation to museology in Maranhão, using decoloniality as a method. To this end, a bibliographic review was conducted to establish a dialogue between museology and decoloniality, discussing the intersection of History, Memory, Cultural Heritage, and their power relations. The methodology included direct observation, the application of questionnaires to interns, and interviews with the current museum administration and the aforementioned artists. This analytical path seeks to contribute to decolonial ways of thinking and doing within museology. The importance of insurgency in Heritage Education is thus highlighted as a means of breaking with coloniality, as it promotes a policy of actions and reflections in favor of equity, respecting differences and the different. It is concluded, therefore, that decolonial museology is grounded in an emancipatory utopia that requires not only a turn, but a gira, since the function of the gira is to bring together multiple presences and knowledges, undoing the cognitive dismantling produced by the colonial burden. A ritual (ebó) of reincarnation that helps us reflect on our identity processes, as well as foster a better recognition of our fratrimônios. This remains a distant perspective in the context of Maranhão, as the study revealed the lack of administrative autonomy of the Museum of Visual Arts of Maranhão, which hinders the adoption of decolonial guidelines. The research also highlighted the precarious state of Maranhão’s cultural institutions and the erasure of local art, constituting practices of epistemicide. The museum is thus defended as a strategic space for dignity, diversity, and social transformation, reinforcing the need for public policies that strengthen decolonial museological processes and expand the right to imagination.